Traumatic Brain Injury Impairs Systemic Vascular Function through Disruption of Inward-Rectifier Potassium Channels. Issue 3 (6th April 2021) - Sackheim, Adrian M; Villalba, Nuria; Sancho, Maria; Harraz, Osama F; Bonev, Adrian D; D'Alessandro, Angelo; Nemkov, Travis; Nelson, Mark T; Freeman, Kalev
Abstract: Trauma can lead to widespread vascular dysfunction, but the underlying mechanisms remain largely unknown. Inward-rectifier potassium channels (Kir2.1) play a critical role in the dynamic regulation of regional perfusion and blood flow. Kir2.1 channel activity requires phosphatidylinositol 4, 5-bisphosphate (PIP2 ), a membrane phospholipid that is degraded by phospholipase A2 (PLA2 ) in conditions of oxidative stress or inflammation. We hypothesized that PLA2 -induced depletion of PIP2 after trauma impairs Kir2.1 channel function. A fluid percussion injury model of traumatic brain injury (TBI) in rats was used to study mesenteric resistance arteries 24 h after injury. The functional responses of intact arteries were assessed using pressure myography. We analyzed circulating PLA2, hydrogen peroxide (H2 O2 ), and metabolites to identify alterations in signaling pathways associated with PIP2 in TBI. Electrophysiology analysis of freshly-isolated endothelial and smooth muscle cells revealed a significant reduction of Ba 2+ -sensitive Kir2.1 currents after TBI. Additionally, dilations to elevated extracellular potassium and BaCl2 - or ML 133-induced constrictions in pressurized arteries were significantly decreased following TBI, consistent with an impairment of Kir2.1 channel function. The addition of a PIP2 analog to the patch pipette successfully rescued endothelial Kir2.1 currents after TBI. Both H2 O2 and PLA2 activity were increased after injury. Metabolomics analysis demonstrated altered lipid metabolism signaling pathways, including increased arachidonic acid, and fatty acid mobilization after TBI. Our findings support a model in which increased H2 O2 -induced PLA2 activity after trauma hydrolyzes endothelial PIP2, resulting in impaired Kir2.1 channel function. Graphical Abstract: